2019
DOI: 10.1101/740837
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Massive parallel variant characterization identifiesNUDT15alleles associated with thiopurine toxicity

Abstract: As a prototype of genomics-guided precision medicine, individualized thiopurine dosing based on pharmacogenetics is a highly effective way to mitigate hematopoietic toxicity of this class of drugs.Recently, NUDT15 deficiency was identified as a novel genetic cause of thiopurine toxicity, and NUDT15-informed preemptive dose reduction is quickly adopted in clinical settings. To exhaustively identify pharmacogenetic variants in this gene, we developed massively parallel NUDT15 function assays to determine variant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 47 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…In recent years NUDT15 has also been shown to be a major player in thiopurine metabolism. Inactivating mutations in NUDT15 are strongly associated with thiopurine toxicity (19), and thiopurine dosage adjustment is recommended based on NUDT15 genotyping (20,21). In addition to the role of NUDT15 in thiopurine hypersensitivity, other studies have suggested that thiopurine-based therapies in patients with WT NUDT15, can be improved by NUDT15 inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years NUDT15 has also been shown to be a major player in thiopurine metabolism. Inactivating mutations in NUDT15 are strongly associated with thiopurine toxicity (19), and thiopurine dosage adjustment is recommended based on NUDT15 genotyping (20,21). In addition to the role of NUDT15 in thiopurine hypersensitivity, other studies have suggested that thiopurine-based therapies in patients with WT NUDT15, can be improved by NUDT15 inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…These variants in TPMT therefore lead to excessive accumulation of thioguanine in the genome, which ultimately causes the severe hematopoietic toxicity observed in patients undergoing thiopurine-based chemotherapy (15)(16)(17)(18)(19). For this reason, it is recommended to adjust the thiopurine dosage according to the results of preemptive TPMT genotyping (20,21).…”
mentioning
confidence: 99%
“…Despite the significance of this work, there are several important caveats: (1) We only used PC9 cells for cytotoxicity screening. The genetic background of this cell line might have had an unwanted influence on the functional interpretation of variants [12,19]. Use of multiple NSCLC cell lines for parallel functional screening can significantly reduce such interference; (2) The expression of the exogenous EGFR variants was higher than that of endogenous EGFR in PC9 cells, which may lead to an overestimation of the TKI resistance of specific variants; (3) The endogenous EGFR of PC9 cells was deleted by CRISPR/Cas9.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, a mutant library is first constructed employing synthetic biology or genome editing methods [11,12], and functional impacts of variants are determined through parallel functional assays. To date, variants of a few clinically actionable genes, such as BRCA1, PPARG, TP53, PTEN, TPMT, NUDT15, SCN5A, CYP2C9, CYP2C19, CXCR4, CCR5, ADRB2, and MSH2 [12][13][14][15][16][17][18][19][20][21][22][23][24], have been extensively studied using the DMS method, highlighting its potential for assessing the TKI sensitivity of rare and potential EGFR mutations. In this study, based on the DMS method, we developed massively parallel cytotoxicity assays and systematically determined the sensitivity landscape of the variants to five EGFR-TKIs (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In this approach, a mutagenesis library of missense variants is constructed that represent all possible amino acid substitutions within a protein and their in vitro functionality is determined. This high-throughput functional screening approach has been successfully applied to NUDT15 and could be conceivably applied to CYP2D6 [111]. Analysis of large datasets is another approach to assign functional effects to these undetermined haplotypes, and is being increasingly carried out to interrogate CYP2D6 [112,113].…”
Section: Novel Approaches To Cyp2d6 Phenotypingmentioning
confidence: 99%